Comparison of the life table and reproduction parameters of the Tetranychus urticae (Acari: Tetranychidea) on five strawberry varieties. Issue 6 (18th August 2018) - Azadi Dana, Elahe; Sadeghi, Amin; Maroufpoor, Mostafa; Khanjani, Mohammad; Babolhavaeji, Hassan; Ullah, Mohammad Shaef
ABSTRACT: The two-spotted spider mite (TSSM), Tetranychus urticae Koch, is an important pest of strawberries grown both in greenhouse and field, and also may be infested at high humid condition. In this study, we evaluated the life history and demographic parameters of TSSM on five varieties (Frenzo, Karsin-Berg, Klassica, Pajaro, and Ventana) of strawberry at a constant temperature of 25 ± 1°C, 75 ± 5% RH and a photoperiod of 16:8 h L: D. Egg-to-female adult development was faster on Karsin-Berg and slower on Klassica variety (17.4 vs. 21.1 days). The oviposition period was longer on Karsin-Berg and shorter on Pajaro variety (27.0 vs. 17.4 days). Fecundity and female adult longevity of TSSM were significantly different among the five varieties of strawberry. Life table parameters provide most comprehensive description on the survival, stage differentiation, and reproduction of the population and they were significantly affected by different varieties of strawberry. The net reproductive rate was the highest on Ventana and lowest on Pajaro. The intrinsic rate of natural increase varied from 0.1067 on Frenzo to 0.1212 day −1 on Ventana. The mean generation time of TSSM were considerably affected by strawberry varieties and the longer generation time was on Frenzo. Based on results of the present study, Frenzo and Pajaro is a less favourable variety for the population growth of TSSM. Research on these five strawberry varieties can be used to improve our understanding of the population dynamics of the pest and thereby develop effective pest management programmes against T. urticae .